Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1365-2516.2007.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of quality of life: menorrhagia in women with or without inherited bleeding disorders

Abstract: The objectives of this study were to identify the impact of menorrhagia on the health-related quality of life (HRQOL) of women in general and those with inherited bleeding disorders and to identify the commonly used tools in assessing quality of life. A review of studies evaluating quality of life in women suffering from menorrhagia was conducted. Data sources used included electronic databases Medline and Embase. Reference lists and bibliographies of the relevant papers and books were hand-searched for additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 30 publications
5
76
1
Order By: Relevance
“…Historically, patient-reported outcomes have not been the primary focus of HMB clinical trials 2 . Although modern trials are more apt to include patient-reported outcome measures, lack of a standard, disease-specific instrument makes interpretation of the results more challenging 9,10 . Determining minimally important changes in HMB has the most relevance for pharmacologic HMB therapies (e.g., hormonal therapies, competitive plasminogen inhibitors, anti-inflammatory drugs), as other treatment options such as hysterectomy or endometrial ablation eliminate or radically diminish MBL 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, patient-reported outcomes have not been the primary focus of HMB clinical trials 2 . Although modern trials are more apt to include patient-reported outcome measures, lack of a standard, disease-specific instrument makes interpretation of the results more challenging 9,10 . Determining minimally important changes in HMB has the most relevance for pharmacologic HMB therapies (e.g., hormonal therapies, competitive plasminogen inhibitors, anti-inflammatory drugs), as other treatment options such as hysterectomy or endometrial ablation eliminate or radically diminish MBL 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Certain questions on nonspecific QOL instruments, such as the Short Form 36 (SF-36), lack relatability for patients with HMB, thus making them suboptimal tools for this population [11][12][13] . Shortcomings in standardized QOL measures have led to a proliferation of questionnaires, although their validity and reliability have not been fully documented 10,12 . Numerous instruments for measuring health outcomes in menorrhagia research have been developed [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…A practical diagnosis of HMB is excessive MBL that is not tolerated by the patient and negatively affects her QOL. The most appropriate methodology and tool for evaluating QOL in patients with HMB continues to be a subject of debate 10 . Certain questions on nonspecific QOL instruments, such as the Short Form 36 (SF-36), lack relatability for patients with HMB, thus making them suboptimal tools for this population [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Nonsteroidal antiinflammatory drugs, hormonal treatment and surgical procedures can effectively reduce menstrual blood loss; however, variable efficacy, relative contraindications, potential adverse effects, or undesired effects on fertility can limit the use of these therapies. 7 Most patients complaining of menorrhagia have no detectable pelvic disease and are diagnosed as cases of dysfunctional uterine bleeding.…”
Section: Introductionmentioning
confidence: 99%